Bloodstain Pattern: An open source of Evidence A Case Study: Muhammad Rashad Bhatti - Ayesha Sarwar; Bhatti, Muhammad Rashad Bhatti (International Journal for Electronic Crime Investigation, 2020)
Abstract: The purpose of this paper is to present a case study of a crime committed in a remote area of Pakistan where a woman was found dead and her death was reported as a suicide. Investigation agency collected the data including the pictures from the crime scene. These pictures were sent to crime scene unit for their recommendations. Forensic experts studied and analyzed these pictures and by applying the techniques of Bloodstain Pattern Analysis (BPA). As blood behaves according to certain scientific principles, trained bloodstain pattern analysts can examine the blood evidence left behind and draw conclusions as to how the blood may have been shed. It is done by examining the distribution, location, shape and size of the bloodstains and it helps in determining about what did or did not happen. Because blood behaves according to certain scientific principles, trained bloodstain pattern analysts can examine the blood evidence left behind [and draw conclusions as to how the blood may have been shed]. BPA provides information not only about what happened, but just as importantly, what could not have happened.A detailed analysis gave enough evidence to the experts that the submitted case was not a suicide rather it was a case of a homicide. The paper will attempt to study the observations of experts while analyzing the bloodstain pattern submitted to them and the conclusions they subsequently drawn, leading towards a clear evidence of a murder case.